210k views
3 votes
Which expression is equal to

Which expression is equal to-example-1
User Mandreko
by
5.7k points

1 Answer

4 votes

Answer:


6i √(3)

Explanation:

To simplify a negative square root, you can rewrite the
√(-27):


√(-27) ==
√(-1 * 27)

Which can then be rewritten itself as:


√(-1) * √(27)

Now, you need to factor the 27, traditionally you will get to remember these but:


√(3 * 9) * i == \sqrt{3 * 3^(2) }* i

As you are square rooting, the
3^(2) can be cancelled and simplified:


3 √(3) * i

Now, as there is already a 2 before the square root, you can simply multiply the 3i by 2:


(3i * 2) √(3) = 6i √(3)

Hope this helps!

User Brandon Wagner
by
6.5k points